2005
DOI: 10.1351/pac200577030559
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of amino acids, sugars, and proteins

Abstract: Abstract:The importance of biomolecules is well recognized nowadays, owing to their application in many industrial processes, particularly in the food, pharmaceutical, and cosmetic industries.Amino acids, carbohydrates, and proteins are the three types of biomolecules considered in this review. Solubilities of several amino acids and sugars have been measured in water and, more recently, in mixed solvents, both with or without salts. Experimental data on partition of proteins in aqueous two-phase systems (ATPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…If these molecules are fully dissolved in water, one can regard them as being in solution and not in suspension. Many proteins are soluble in water (e.g., Osborne, 1910;Macedo, 2005; Sect. S1.1), but single protein molecules are far larger than e.g., salt ions or low molecular weight saccharides.…”
Section: Solubility Of Inmsmentioning
confidence: 99%
“…If these molecules are fully dissolved in water, one can regard them as being in solution and not in suspension. Many proteins are soluble in water (e.g., Osborne, 1910;Macedo, 2005; Sect. S1.1), but single protein molecules are far larger than e.g., salt ions or low molecular weight saccharides.…”
Section: Solubility Of Inmsmentioning
confidence: 99%
“…This type of studies may also help in understanding the solubility behavior and solvation chemistry of related biomolecules. For quite a long time, several studies on the solubilities of different amino acids have been carried out in water, in mixed solvents and in both with or without salts using several chemical and thermodynamic models under different experimental conditions [2][3][4][5][6][7]. It has been observed that experimental temperature [2,4], polarity of the solvents [8][9][10], ionic strength [3,11], acidity or alkalinity of the media [4,6,9,12], etc., affect the solubility of amino acids and hence the thermodynamics of solvation significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility data for different sugars in water have been measured and published since the late years of the 19th century 12. Additionally, the solubility of common sugars (glucose, fructose, lactose, and sucrose) in methanol–water and ethanol–water mixtures is also available in the literature 13–17.…”
Section: Introductionmentioning
confidence: 99%